Correlation of fouling mechanism with enzymatic hydrolysis in an enzyme-membrane integrated system for high sugar permeation from pineapple leaves - Kohmalam, Ayanasamy (2023)
Solid waste management is a critical issue for society worldwide. Glass is widely used in our daily life, and around 10 million tonnes of waste and crushed glass will be produced in large cities worldwide, which compose about 3–5% of all household wastes. The use of waste glass as a component in asphalt mixture may help alleviate the burden faced by environmental authorities. Thus, this research was presented to investigate the performance of hot mix asphalt containing glass powder as bitumen modifier. The glass was ground to size passing 30μm sieve was used in this study. Bitumen 60/70 penetration grade was prepared to mix with variance percentage of glass powder at 2, 4, 6, 8 and 10%. The chemical and physical properties of glass powder as bitumen modifier was evaluated with various tests such as fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray fluorescence (XRF), field emission scanning electron microscopy (FESEM), scanning electron microscopy (SEM), softening point, penetration test and penetration index. Mechanical properties are then evaluated to determine the Marshall strength, indirect tensile strength, moisture susceptibility, Cantabro, resilient modulus and dynamic creep modulus. Design of experiment was used to analyse all collected data and determine the optimum percentage of additives. Response Surface Methodology was employed to produce mathematical models on the strength and moisture susceptibility of hot mix asphalt incorporating glass powder. The findings from chemical and physical properties reveals that the main chemical compositions of the glass powder are silicon oxide (SiO2). The glass powder as bitumen modifier was found to be effective in improve the mechanical properties of hot mix asphalt. Glass powder as bitumen modifier improves the Marshall stability and flow of asphalt mixture, indicates that the glass powder was able to resist deformation under imposed loads. Next, 8% glass powder shows higher indirect tensile strength which leads to improve the cracking resistance. Moreover, the tensile strength ratio of glass powder demonstrates the same pattern as indirect tensile strength. This is due to glass powder had better resistance to stripping and less susceptible to moisture damage. Furthermore, the stiffness is enhanced by the addition of 10% glass powder, which also increases the resilient modulus and the dynamic creep modulus, hence enhancing the resistance to fatigue and rutting. For statistical analysis, the strength and moisture susceptibility of asphalt mixtures have a curvilinear relationship with glass powder. Both factors had correlated using a second-order polynomials correlation, and resulting the mixed correlation has strong correlation with R2 value above 0.90. The findings show that the bitumen modifier with 4-10% of glass powder had improved the road pavements in mechanical performance. Finally, the study showed that hot mix asphalt containing glass powder has the potential to be used in the road industry.